PENGARUH MODEL PEMBELAJARAN KOOPERATIF DAN TIPE KEPRIBADIAN TERHADAP HASIL BELAJAR GEOGRAFI PADA SISWA KELAS XI SMA GAJAH MADA MEDAN - Judika Manik (Universitas Quality, 2018)
This research was conducted at the senior high school students of class XI SMA Gajah MadaTerrain semester academic year 2013/2014 on learning outcomes geography. The samplingtechnique used by cluster random sampling based on the type of personality of students, sothat the study sample in each study group consisted of 42 to 42 people for the experimentaland control groups. The method used is a quasi experiment with 2 x 2 factorial analysistechnique used is the analysis of variance of two lanes with a significance level α = 0.05 by Ftest, further testing using Scheffe test.The research findings show (1) Results of Geography Students learn self-Terrain hope taughtby cooperative learning model TSTS higher than the learning model of Jigsaw at significancelevel = 0.05 to 4.08 and Ftabel Fh = 3.96, jadiFhitung> Ftable = 4.08> 3.96. The hypothesishas been verified Ha Ho accepted and rejected. (2) the results of the calculation of thedifference between the results of learning geography students who have personality typesextrovert and introvert personality type at significance level α = 0.05 at 27.45 and Ftabel Fh =3,96jadi F count> F table = 27.45 > 3.96, the hypothesis has been tested kebenaranya Ha Hoaccepted and rejected, (3) the average size of each learning outcome study Geography45,42dan A1B2 A1B1 = = 36.96 while 39,71dan A2B2 A2B1 = = 38.05. Factorial ANOVAcalculation results obtained calculation results Fh = 14.01 and the price table is Ft (0.05)(1.80) = 3.96, so that it can be stated Fh (14.01)> Ft (3.96), then hypothesis has been verifiedaccepted Ha Ho is rejected.